Highly efficient catalytic hydrogenolysis of lignin model compounds over hydrotalcite-derived Ni/Al2O3 catalysts. (1st April 2023) - Gao, Han-Bing; Qiu, Le-Le; Wu, Fa-Peng; Xiao, Jian; Zhao, Yun-Peng; Liang, Jing; Bai, Yong-Hui; Liu, Fang-Jing; Cao, Jing-Pei
Graphical abstract: Highlights: Highly active Ni/Al2 O3 catalysts were synthesized from LDHs precursors. Ni/Al2 O3 -500 exhibited excellent catalytic performance in the hydrogenolysis of DPE. Various lignin model compounds can be completely converted to monomeric products. Ni/Al2 O3 -500 possesses excellent stability and recyclability. Abstract: Catalytic hydrogenolysis of CO bonds in lignin provides a promising route to produce high value-added biofuels and chemicals. However, designing highly active and stable catalysts for this process is still a challenge. Herein, a series of Ni/Al2 O3 catalysts were synthesized by calcination and reduction of layered double hydroxide precursors, and their activities were evaluated in the catalytic conversion of lignin-derived compounds. Diphenyl ether was completely converted with a 100% monomeric selectivity (cyclohexane and cyclohexanol) over the optimized Ni/Al2 O3 -500 under the optimal conditions of 200 ℃, 0.5 MPa H2 and 1.5 h, indicating the excellent catalytic activity in the cleavage of CO bonds of the catalyst. The excellent catalytic performances of Ni/Al2 O3 -500 were originated from its relatively large specific surface area, well-developed porosity, small crystallite size, high Ni 0 concentration and strong interaction between the active metal and support. The reusability experiments show that Ni/Al2 O3 -500 possesses a relatively high stability for six reuses. Moreover, various lignin model compounds can be completely converted to corresponding monomeric products over Ni/Al2 O3 -500, indicating the applicability of this ingenious catalyst. The application of the hydrotalcite-derived Ni-based catalysts with high activity and stability provides a promising approach for the efficient hydrogenolysis of lignin derivatives.